Non-lytic spread of poliovirus requires the nonstructural protein 3CD - David Aponte-Diaz; Jayden M. Harris; Tongjia Ella Kang; Victoria Korboukh; Mohamad S. Sotoudegan; Jennifer L. Gray; Neela H. Yennawar; Ibrahim M. Moustafa; Andrew Macadam; Craig E. Cameron (mBio)
ABSTRACT Non-enveloped viruses like poliovirus (PV) have evolved the capacity to spread by non-lytic mechanisms. For PV, this mechanism exploits the host secretory autophagy pathway. Virions are selectively incorporated into autophagosomes, double-membrane vesicles that travel to the plasma membrane, fuse, and release single-membrane vesicles containing virions. Loading of cellular cargo into autophagosomes relies on direct or indirect interactions with microtubule-associated protein 1B-light chain 3 (LC3) that are mediated by motifs referred to as LC3-interaction regions (LIRs). We have identified a PV mutant with a severe defect in non-lytic spread. An F-to-Y substitution in a putative LIR of the nonstructural protein 3CD prevented virion incorporation into LC3-positive autophagosomes and virion trafficking to the plasma membrane for release. Using high-angle annular dark-field scanning transmission electron microscopy to monitor PV-induced autophagosome biogenesis, for the first time, we show that virus-induced autophagic signals yield normal autophagosomes, even in the absence of virions. The F-to-Y derivative of PV 3CD was unable to support normal autophagosome biogenesis. Together, these studies make a compelling case for the direct role of a viral nonstructural protein in the formation and loading of the vesicular carriers used for non-lytic spread that may depend on the proper structure, accessibility, and/or dynamics of its LIR. The studies of PV 3CD protein reported here will hopefully provoke a more deliberate look at the presence and function of LIR motifs in viral proteins of viruses known to use autophagy as the basis for non-lytic spread.IMPORTANCEPoliovirus (PV) and other enteroviruses hijack the cellular secretory autophagy pathway for non-lytic virus transmission. While much is known about the cellular factors required for non-lytic transmission, much less is known about viral factors contributing to transmission. We have discovered a PV nonstructural protein required for multiple steps of the pathway leading to vesicle-enclosed virions. This discovery should facilitate the identification of the specific steps of the cellular secretory autophagy pathway and corresponding factors commandeered by the virus and may uncover novel targets for antiviral therapy.